PERAN ALKHAIRAAT DALAM PENGEMBANGAN DAKWAH DI KABUPATEN TOJO UNA-UNA - Hidayat, Mokh. Ulil (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi; Vol 12 No 1 (2016), 2016)
The organization of Alkhairaat develops Islamic preaching through education, and participates directly into society. The islamic preaching of Alkhairaat is a continuity of the process that has occurred for decades ago. Today, Alkhairaat faces a dynamic reality; therefore, it makes the organization change, especially in terms of the management, content, targets, strategy, media, of Islamic preaching, in order to achieve its goal and become a source of reference for society. In addition, Alkhairaat should do regular evaluation to the practices that have been implemented so far. By regular evaluation, Akhairaat can see the strength, opportunities and threats.